The European Ambition: The Group of the European People’s Party and European Integration - Bardi, Luciano,; Gagatek, Wojciech,; Germond, Carine,; Johansson, Karl Magnus,; Kaiser, Wolfram,; Sassano, Silvia, (Nomos Verlagsgesellschaft mbH & Co. KG, 2020)
This book traces the EPP Group’s institutional, organisational and political trajectory in the European Parliament, focusing on the period after the first direct elections in 1979. In doing so, it sheds light on the functioning of parliamentary party groups, while at the same time creating the conditions for a better understanding of their role in the process of European integration and in the EU’s political system.Based on the conceptual framework of different disciplines—history, political science, European studies and political sociology—this book is the outcome of a research project involving scholars with diverse academic backgrounds and from different EU countries.